The comparative analysis of the cytogenetic and morphometric characteristics of some mammals - Hakhiyev Agil; Rajabova Sevinj; Mammadov Ayaz (BIO Web of Conferences)
5 species of the Meriones genus are known in Azerbaijan. In these species (Libyan Jird ( Meriones libycus Lichtenstein, 1842)), the studying of the chromosomal homology and intraspecies problems is one of the actual issues. Based on the literature data about the species of Libyan Jird (Meriones libycus Lichtenstein, 1842), it turns out that very few researches have been conducted in the physical-geographical region of Jeyranchol - Ajinohur. There is a need to the ecological, morphological and cytogenetic researches of this species in the research area and the researches are carried out by us. At the same time, there is a need of a comparative morphometric researching of the Common Pipistrelle (Pipistrellus pipistrellus Schreber, 1774) species in the research areas, because the comparative morphometric measurements of the species have not been researched in the research areas. In the areas of the Jeyranchol - Ajinohur geographical region, the comparative morphometric measurements of the Common Pipistrelle species are investigating by us. Both areas are located in the semi-desert zone and are characterized by relatively different landscape, vegetation, substrate, altitude and weather conditions (especially precipitation). The Gobustan region is the area with little precipitation and the most wind, and more characterized by the glasswort-wormwood-ephemeral plants. Jeyranchol has wormwood- caperbushes, sparsely shrubby xerophytic vegetation.